Cyclic deformation behavior of a high zinc-containing cast magnesium alloy. (August 2019) - Mohammed, S.M.A.K.; Li, D.J.; Zeng, X.Q.; Chen, D.L.
Graphical abstract: Highlights: A distinctive microstructure with network Mg32 (Al, Zn)49 phase is observed. Tensile properties of this alloy are superior to several commercial alloys. The alloy exhibits almost symmetrical stress-strain hysteresis loops. Cyclic and monotonic stress-strain curves are largely overlapped. Fatigue life can be adequately predicted via an energy based model. Abstract: The objective of the present study was to evaluate strain-controlled low cycle fatigue behavior of a high zinc-containing Mg-10Zn-5Al (wt.%) cast magnesium alloy in relation to the microstructure characterized via EBSD and XRD. The addition of Zn with a Zn/Al ratio of ∼2 suppressed the presence of β-Mg17 Al12 phase, and the as-cast alloy consisted mainly of primary α-Mg and eutectic-like τ-Mg32 (Al, Zn)49 phase in a characteristic network form. The alloy exhibited superior tensile properties compared with several commercial cast alloys. Unlike extruded magnesium alloys, the alloy exhibited almost symmetrical stress-strain hysteresis loops due to the presence of τ-Mg32 (Al, Zn)49 phase and nearly random textures. Although slight cyclic softening occurred at higher strain amplitudes, cyclic stabilization basically remained. This was also reflected by the nearly overlapped cyclic and monotonic stress-strain curves. The fatigue life predicted via strain energy based approach was in good agreement with the experimental value. Fatigue crack initiated from the near-surface imperfections, and crack propagation was characterized by fatigue striation-like features along with tear ridges.